2017
DOI: 10.1186/s12885-017-3847-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics based analysis to predict local control and survival in hepatocellular carcinoma patients treated with volumetric modulated arc therapy

Abstract: BackgroundTo appraise the ability of a radiomics based analysis to predict local response and overall survival for patients with hepatocellular carcinoma.MethodsA set of 138 consecutive patients (112 males and 26 females, median age 66 years) presented with Barcelona Clinic Liver Cancer (BCLC) stage A to C were retrospectively studied. For a subset of these patients (106) complete information about treatment outcome, namely local control, was available. Radiomic features were computed for the clinical target v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 37 publications
3
60
0
Order By: Relevance
“…The model indicates the potential of MRI-based texture analysis at arterial-and venous-phase MRI for the early prediction of progressive disease after TARE Cozzi et al [106] To predict overall survival and local control Non-contrast CT…”
Section: Monitoring/follow-upmentioning
confidence: 99%
See 2 more Smart Citations
“…The model indicates the potential of MRI-based texture analysis at arterial-and venous-phase MRI for the early prediction of progressive disease after TARE Cozzi et al [106] To predict overall survival and local control Non-contrast CT…”
Section: Monitoring/follow-upmentioning
confidence: 99%
“…First promising results regarding the predictive potential of radiomics for local response after radiotherapy and TACE have recently been demonstrated [105][106][107] and are listed in Table 4. Treatment response of liver metastases after TACE has been determined using a radiomics-based analysis resulting in area under the curve (AUC) in receiver operating characteristics (ROC) of up to 0.83 [105].…”
Section: Monitoring/follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results showed that two features have good accuracy in the prediction of local control: the area under the curve of energy and Gray‐level Non‐Uniformity (GLNU), which were 0.6659 and 0.6396, respectively. For the prediction of overall survival, the area under the curve of the feature named compacity reached 0.8014 29 . Another study quantitatively evaluated radiation‐induced changes of internal obturator muscles after radiotherapy for prostate cancer.…”
Section: Application Of Radiomics In Radiotherapymentioning
confidence: 99%
“…6569 In the context of lung cancer, radiomics has successfully allowed detection of malignancies in screening CT scans, 53 provided a means to differentiate between benign and malignant lesions, 51 enabled the prediction of risk of recurrence post-therapy, 52 and provided a means to noninvasively assess response to therapy 70 as well as helped to identify patients who would most benefit from therapy. 28 …”
Section: Radiomics As a Novel Tool To Quantitatively Analyze Tumor Immentioning
confidence: 99%